(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A study was conducted in Calcareous Low Ganges River Floodplain Soil (AEZ 12) at Regional Pulses Research (RPRS), Madaripur during the Rabi season of 2010-12.The objectives were to evaluate the effect of Zinc (Zn) and Boron (B) on the yield and yield contributing characters of lentil (Lens culinaris Medic) and to estimate the optimum dose of Zn and B for yield maximization. There were 16 treatment combinations comprising four levels each of Zinc (0, 1.0, 2.0 and 3.0 kg/ha) and Boron (0, 0.5, 1.0 and 1.5 kg/ha) along with a blanket dose of N20 P16 K30 S10 kg/ha were used. The treatments were arranged viz. T1= Zn0B0; T2= Zn0B0.5; T3= Zn0B1.0; T4= Zn0B1.5; T5= Zn1.0B0; T6= Zn1.0B0.5; T7= Zn1.0B1.0; T8= Zn1.0B1.5; T9= Zn2.0B0; T10= Zn2.0B0.5; T11= Zn2.0B1.0; T12= Zn2.0B1.5; T13= Zn3.0B0; T14= Zn3.0B0.5; T15= Zn3.0B1.0 and T16= Zn3.0B1.5. The experiment was laid out in RCBD with three replications. Results showed that the combination of Zn3.0B1.5 produced significantly higher seed yield (1156 kg/ha). The lowest seed yield (844 kg/ha) was found in control (Zn0B0) combination. The combined application of zinc and boron were superior to their single application. Therefore, the combination of Zn3.0B1.5 may be considered as suitable dose for lentil cultivation in Bangladesh. But from regression analysis, the optimum treatment combination was Zn2.85B1.44 for Madaripur, Bangladesh. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22538 Bangladesh J. Agril. Res. 39(4): 591-603, December 2014